Analytical validation of automated multiplex chromogenic immunohistochemistry for diagnostic and predictive purpose in non-small cell lung cancer. (April 2022) - Ilié, Marius; Beaulande, Mélanie; Long-Mira, Elodie; Bontoux, Christophe; Zahaf, Katia; Lalvée, Salomé; Hamila, Marame; Benzaquen, Jonathan; Cohen, Charlotte; Berthet, Jean-Philippe; Marquette, Charles-Hugo; Lassalle, Sandra; et al.
Highlights: mIHC maximizes tissue preservation for further molecular analyses. The validation of mIHC for routine clinical laboratory processes is mandatory. We validated two mIHC assays to characterize NSCLC histotypes predictive biomarkers. Standardized protocols are available on a widely available IHC autostainer. Abstract: Objectives: The evaluation of an increasing number of diagnostic and predictive markers is playing a central role in precision thoracic oncology. Multiplex immunohistochemistry (mIHC), alongside next-generation sequencing, is ideally situated for this purpose and maximizes tumor tissue preservation for molecular analyses that use increasingly large panels. However, the standardization and validation of mIHC that supports routine clinical laboratory processes are mandatory. After a previous proof-of-concept study, we now (i) optimized two automated four-plex assays on a commercially available IHC autostainer for use in daily practices worldwide and (ii) evaluated the repeatability and concordance of the assessment of the cell density. Patients and methods: Two four-plex mIHC assays [i) TTF1, p40, PD-L1, CD8; and, ii) ALK, ROS1, BRAFV600E, NTRK] were optimized on the BenchMark ULTRA autostainer (Ventana Medical Systems, Inc.), as determined in comparison to conventional IHC chromogenic assays. Intra-site repeatability was evaluated on serial tumor sections from non-small cell lung carcinomas (NSCLC). The concordance was assessed by linear fit to plots of the percentage staining evaluated on tumor sections from 89 NSCLC patients. Results: Following optimization, an average concordance for a staining rate of 95.4% was achieved between conventional IHC and mIHC across all selected markers. Assessment of intra-site repeatability showed strong concordance for all these markers (average, R 2  = 0.96; P -value < 0.001). Conclusions: Our optimized mIHC assay gave a sensitive and repeatable assessment of two panels of eight diagnostic and predictive biomarkers for NSCLC. The availability of standardized protocols to determine these biomarkers on a widely available IHC platform will expand the number of pathology laboratories able to determine the eligibility of patients with NSCLC for targeted treatment or immunotherapy in a reliable and concordant manner, thus providing a unique sample-sparing tool to characterize limited tissue samples in thoracic oncology.